GENETIC ARCHITECTURE OF YIELD AND ITS COMPONENTS IN BRINJAL (SOLANUM MELONGENA L.) - ANKIT D. GADHIYA , K. N. CHAUDHARI , P. M. SANKHLA , Y. A. VIRADIYA BHAMINI PAREKH (The Bioscan, 2015)
A field experiment was carried out comprised of 10 parents, 45 hybrids and commercial hybrid ABH-1 (check) during 2014-15, at RHRS, NAU, Navsari. The analysis of variance for all the traits revealed that parents were found to be significant for all the traits studied indicating presence of considerable amount of genetic variability in the parental material tested. IC 074224 x IIHR 635 (60.69), Surati Ravaiya Pink x Arka Neelkanth (58.81) and IIHR 635 x Arka Neelkanth (55.08) showed significant and desirable heterobeltiosis for fruit yield. Combining ability studies revealed non additive type of gene action involved in the expression of traits. IC 074224, Punjab Barsati and IC 11066-2 were good general combiners for fruit yield per plant. The ratio of gca variance/ sca variance were observed less than unity for all the characters which revealed the predominance of non-additive gene action. The overall analysis based on gca effect, sca effect, heterobeltiosis and standard heterosis revealed that parents IC 074224, IC 11066-2 and IIHR 635 and crosses IC 074224 x IC 11066-2, Surati Ravaiya (Pink) x Arka Neelkanth and IIHR 635 x Arka Neelkanth found promising for future breeding programme.